KARAKTERISTIK BROWNS GAS HASIL ELEKTROLISIS H2O DENGAN MENGGUNAKAN NAHCO3 - Ena Marlina (Jurnal Teknik Mesin, 2013)
Global warming issues and the depletion of fossil fuel reserves encourage the finding of new alternative fuel that is renewable, easy to find, manage and expected able to shift the dependency to the fossil fuel and alternative fuel that has environmentally friendly emission. One of alternative fuel such as HHO (Browns Gas), results of water electrolysis by using electric current. Electrolysis is process of water molecule (H2O) disentanglement become hydrogen (H2) and oxygen (O2) with reaction triggering energy of electricity. The process can be run when two electrodes was placed in water and direct current pass through between the two electrodes. Hydrogen was formed at the cathode, while oxygen at anode. And to improve the conductivity of electricity and production of HHO gas (Brown gas) that produced in the process, it need additional catalyst, in the research was NaHCO3 (Sodium Bicarbonate) with percentage variation of 2,5; 5; 7,5; 10; 12,5 and 15%, that was dissolved in the aquadest water. The results showed that the more NaHCO3 dissolved in the water the higher electric current that passing through in the electrolyte. NaHCO3 10% percentage has the highest HHO generator efficiency, that was 18.954%.